EFFECT OF AEROBIC EXERCISE ON BRAIN-DERIVED NEUROTROPHIC FACTOR AND COGNITIVE FUNCTION IN OLDER ADULTS - Ade Mayra Hosiana; Nila Wahyuni (Program Studi Magister Fisiologi Keolahragaan, Fakultas Kedokteran, Universitas Udayana, 2023)
Aging is a natural process experienced by all living things. In aging, there is a decrease in the functions of various organ systems in the human body, including a decrease in brain function. Decreased brain capacity is associated with various risks of diseases such as dementia, which can impair the quality of life. One of the proteins in the brain that related to brain plasticity, learning, memory abilities, and cognitive function is brain-derived neurotrophic factor (BDNF). Aerobic exercise is said to be able to increase serum BDNF levels and cognitive function in elderly individuals. This study was conducted using a literature review method. We review and compare recent journals discussing the relationship between aerobic exercise and its effect on BDNF levels and cognitive function. Aerobic exercise has been shown to increase BDNF levels in the elderly. Aerobic exercise also shown to improve several components of cognitive function. In conclusion, aerobic exercise has a positive effect on brain health, and it is recommended for older adult engaging moderate aerobic exercise, 150 minutes weekly. Keywords: aerobic exercise; BDNF; cognitive function